2011
DOI: 10.1016/j.metabol.2011.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Nebivolol improves insulin sensitivity in the TGR(Ren2)27 rat

Abstract: Objective Hypertension is often associated with increased oxidative stress and systemic insulin resistance. Use of β adrenergic receptor blockers in hypertension is limited due to potential negative influence on insulin sensitivity and glucose homeostasis. We sought to determine the impact of nebivolol, a selective vasodilatory β1adrenergic blocker, on whole-body insulin sensitivity, skeletal muscle oxidative stress, insulin signaling and glucose transport in the transgenic TG(mRen2)27rat (Ren2). This rodent m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
14
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 31 publications
5
14
0
1
Order By: Relevance
“…As previously described (25,51), SBP was elevated in the Ren2-C group compared with the SD-C group (207 Ϯ 8 vs.…”
Section: Experimental Parameterssupporting
confidence: 70%
See 1 more Smart Citation
“…As previously described (25,51), SBP was elevated in the Ren2-C group compared with the SD-C group (207 Ϯ 8 vs.…”
Section: Experimental Parameterssupporting
confidence: 70%
“…Nebivolol is a highly cardiac-selective ␤ 1 -adrenergic receptor blocker that contributes to vasodilation by increasing bioavailable NO through its coupling to the ␤ 3 -receptor subtype (13). It has been reported that nebivolol treatment leads to reductions in NADPH oxidase activity in the heart and vascular tissue (13,32,41,43), and recent work has highlighted improvements in insulin metabolic signaling and enhancement in bioavailable NO in skeletal muscle (25) and kidney tissue (51) in a transgenic (TG) (mRen2)27 (Ren2) rat model. This Ren2 rat manifests tissue overexpression of the mouse renin gene and tissue ANG II with elevations in SBP, insulin resistance, and increases in myocardial oxidative stress and diastolic dysfunction (14,50).…”
mentioning
confidence: 99%
“…In earlier days, it was demonstrated that enhanced kinetics of the reaction between mouse renin and rat angiotensinogen are one of pathophysiological mechanism for this model. 39,40 Recently, this animal model was reported to have various pathophysiological features such as insulin resistance, [41][42][43] left ventricular dysfunction, 44,45 nonalcoholic fatty liver disease-like significant hepatic steatosis with increased hepatic reactive oxygen species, lipid peroxidation, steatohepatitis, and fibrosis 46 as a result of tissue RAS overactivation. We generated transgenic ARen2 overexpression mice with a C57BL/6J background, which endogenously have only the Ren1C renin gene.…”
Section: July 2014mentioning
confidence: 99%
“…Высокая клиническая эффективность небиво-лола при различных сердечно-сосудистых заболе-ваниях -АГ, ИБС, в том числе у больных с СД на сегодняшний день имеет большую доказатель-ную базу -более 70 исследований [30][31][32][33][34][35].…”
Section: российский кардиологический журнал № 4 (102) | 2013unclassified